2016
DOI: 10.1667/rr14406.1
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Radiation-Induced Coagulopathy and New Findings to Support Potential Prevention Strategies and Treatments

Abstract: Results from our recent studies have led to the novel hypothesis that radiation-induced coagulopathy (RIC) and associated hemorrhage occurring as part of the acute radiation syndrome (ARS) is a major cause of death resulting from radiation exposure in large mammals, including humans. This article contains information related to RIC, as well as potential strategies for the prevention and treatment of RIC. In addition, new findings are reported here on the occurrence of RIC biomarkers in humans exposed to radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 117 publications
1
29
0
Order By: Relevance
“…Previous studies investigating conventional RT and IMRT techniques have reported a decrease in platelet count following treatment, thus corroborating the results of the present study (7,15,38,39). Furthermore, it has been demonstrated that sub-lethal radiation doses may result in abnormal hemostasis characteristics and coagulation biomarker values observed up to 21 days post-irradiation (40). Therefore, the post-RT decrease in platelet counts observed in the present study may be due to the suppressive effect of radiation on the hematopoietic system in the acute phase.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies investigating conventional RT and IMRT techniques have reported a decrease in platelet count following treatment, thus corroborating the results of the present study (7,15,38,39). Furthermore, it has been demonstrated that sub-lethal radiation doses may result in abnormal hemostasis characteristics and coagulation biomarker values observed up to 21 days post-irradiation (40). Therefore, the post-RT decrease in platelet counts observed in the present study may be due to the suppressive effect of radiation on the hematopoietic system in the acute phase.…”
Section: Discussionsupporting
confidence: 92%
“…162 The use of anticoagulants such as heparin has been investigated, but the results to date have been mostly insignificant and generally inconsistent. 163 In contrast, the TM-APC pathway is a hopeful target for preventing or treating radiation toxicity in normal tissues using strategies aimed at restoring or preserving endothelial TM or replacing protein C. 156,164,165 Also, thrombin inhibition has been investigated as a strategy to minimise the side-effects of RT. The recombinant thrombin inhibitor hirudin has shown a protective effect against small bowel radiation toxicity in a model of localised small bowel radiation in rats.…”
Section: Decreasing Coagulopathymentioning
confidence: 99%
“…Fibrinogen deficiency suppresses the development of early and delayed radiation-induced enteropathy, characteristically mediated by endothelial injury, suggesting a role for fibrinogen in mediation of endothelial injury. 35,36 Oxidized low-density lipoprotein (ox-LDL) augments radiation-induced phenotypic changes like upregulation of alpha-smooth muscle actin (α-SMA), fibroblast-specific protein-1 (FSP-1), and vimentin. This transition to mesenchymal phenotype favors acceleration of atherosclerosis.…”
Section: Blood-based Biomarkersmentioning
confidence: 99%
“…Fibrinogen acts as an acute indicator of radiation‐induced activation of the coagulation cascade. Fibrinogen deficiency suppresses the development of early and delayed radiation‐induced enteropathy, characteristically mediated by endothelial injury, suggesting a role for fibrinogen in mediation of endothelial injury . Oxidized low‐density lipoprotein (ox‐LDL) augments radiation‐induced phenotypic changes like upregulation of alpha‐smooth muscle actin (α‐SMA), fibroblast‐specific protein‐1 (FSP‐1), and vimentin.…”
Section: Blood‐based Biomarkersmentioning
confidence: 99%